Pengaruh Pemberian Kunyit Asam Terhadap Dismenore - Cahyono, Aris Dwi (Jurnal AKP, 2012)
Dysmenorrhea is menstrual pain before or during menstruation, to make these women can not work and just sleep. Frequent pain in conjunction with nausea, headaches, feeling faint, irritability. Dysmenorrhea experienced by 95% of women of reproductive age while secondary dysmenorrhea is more rare and occurs in 25% of women who experience dysmenorrhea. The exact cause is unknown suspected dysmenorrhea psychological factors contribute significantly to the emergence of pain. The purpose of this study is to analyze the benefits turmeric acid against dysmenorrhea in SMP Negeri 2 Kediri Grogol. In this study using an experimental research design Pre. Population of more than 40 people and taken samples of 10 people in SMP Negeri 2 Grogol Kediri.Penelitian held on May 10 to 15, 2010 with purposive sampling technique. Collecting data for independent variables namely turmeric acid using a glass ukur.sedangkan for dependent variables using a ruler and then analyzed using cross tabulation. The results in getting the results that the 10 respondents aged between 12 -14 years before the given therapy pain scale is the scale of turmeric acid l (susceptible mild pain scale 1-4) and scale 6 (5-7 pain scale was vulnerable), after a given therapy on the pain scale sour turmeric respondents declined to a scale of 0 (no pain) and scale 4 (susceptible pain scale 1 - 4 mild). And proved it does show that turmeric acid influential in overcoming dysmenorrhea. It can be concluded that the therapeutic effect of turmeric have acid in decreasing menstrual pain so that women could apply this therapy if menstrual pain with a level of mild or moderate pain.